2016
DOI: 10.1007/s11814-016-0032-7
|View full text |Cite
|
Sign up to set email alerts
|

Generation of micro- and nano-bubbles in water by dissociation of gas hydrates

Abstract: Gas hydrate crystals have a structure in which one molecule is enclathrated in a cage of water molecules.When such a crystal dissociates in water, each enclathrated molecule, generally vapor at standard temperature and pressure, directly dissolves into the water. After the solution is supersaturated, excess gas molecules from further dissociation would start forming small bubbles called micro-and nano-bubbles (MNBs). However, it is difficult to identify such small bubbles dispersed in liquid because they are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
83
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(106 citation statements)
references
References 27 publications
14
83
1
Order By: Relevance
“…Since the decomposition behavior is largely governed by the supersaturation of melt water in the vicinity to GH surface, the differences in the solubility and diffusion coefficients will influence the shape of the compositional gradient, but the phenomena are expected to be qualitatively the same. Indeed, molecular dynamics and electron microscopic work on methane hydrate decomposition have repeatedly observed the formation of nano‐ to micro‐ scale gas bubbles which may be the vesicles for the metastable enrichments in the liquid state [ Bagherzadeh et al ., ; Uchida et al ., , ]. Persistence and size of such nano‐bubbles is likely to be somewhat different for Xe and CH 4 systems.…”
Section: Discussionmentioning
confidence: 99%
“…Since the decomposition behavior is largely governed by the supersaturation of melt water in the vicinity to GH surface, the differences in the solubility and diffusion coefficients will influence the shape of the compositional gradient, but the phenomena are expected to be qualitatively the same. Indeed, molecular dynamics and electron microscopic work on methane hydrate decomposition have repeatedly observed the formation of nano‐ to micro‐ scale gas bubbles which may be the vesicles for the metastable enrichments in the liquid state [ Bagherzadeh et al ., ; Uchida et al ., , ]. Persistence and size of such nano‐bubbles is likely to be somewhat different for Xe and CH 4 systems.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the short standing time, the existing gas in the water phase before reformation cannot completely strip the water phase. 56 The stored gas would promote hydrate reformation. 58 Combining Figure 6 and Table 2, it can be found that the induction time at the 1 °C test temperature in the first formation was shorter than those at 3 and 5 °C.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Uchida et al have found that the storage period of 200 min is most conducive to the hydrate reformation. 24,56 The test temperatures of hydrate formation were 1, 3, and 5 °C.…”
Section: Methodsmentioning
confidence: 99%
“…However, various substances readily accumulate at the interface [ 7 ], as shown by the impurity deposits in Figure 1 , and such a change at the interface should decrease the air/water interfacial tension. As a result, the actual internal pressure would be lower than that predicted by use of the air/water interfacial tension of bulk water [ 16 ]. Therefore, the bubble internal pressure in an actual solution should be smaller than that estimated from Equation (2).…”
Section: Resultsmentioning
confidence: 99%
“…We just briefly describe the sample-preparation for the freeze-fracture replicas and TEM observations here as the details are described in [ 6 , 7 , 16 ]. Each frozen sample (at liquid nitrogen temperature) is placed in a freeze-etching device (JEOL, Tokyo, Japan, type JFD-9010), and fractured by a knife edge in a vacuum chamber at a temperature of about 150 K and a pressure of about 10 −5 Pa.…”
Section: Methodsmentioning
confidence: 99%